The mimicry antigens of bronchopulmonary system as factors of autoimmune process initiation in childhood bronchial asthma - Chernuskiy, V; Popov, N; Govalenkova, O; Letyago, A; Kashina-Yarmak, V; Tolmachova, S; Popova, A (Annals of Mechnikov's Institute, 2019)
Introduction. Microorganisms, isolated from the sputum of children with bronchial asthma (BA) in the exacerbation period, are able to acquire mimicry antigens of the trachea, bronchi and lung tissue, and have sensitizing effect on the organism of the child not only through the truly microbial (viral) antigens, but through the acquitted mimicry antigens of the cellular and tissue structures of the bronchopulmonary system, thus shifting the pathological process towards autoimmunity. Materials & methods. A microbiological study of the sputum obtained from the 135 examined children with BA aged 6 to 14 years in the exacerbation period. The disease diagnosis was established according to the protocol and directive of the Ministry of Health of Ukraine from 08.10.2013 № 868. It was established that 45 children had non – atopic asthma, 46 – mixed type asthma (MTBA) and 44 – atopic form of BA (ATBA). Microbiological studies of the sputum were carried out with the help of the commonly accepted methods: plating onto the solid and liquid culture mediums with the subsequent strains isolation, microscopy, biochemical and serological identification. Strains identification was carried out according to the taxonomic tests of the Berge microorganism index. In order to determine the presence of mimicry antigens in the examined strains we have prepared hyperimmune rabbit serums to the trachea, bronchi, and lung tissue antigens. Section samples obtained from the accidentally deceased children with the І(0) blood type 2-4 hours after the moment of death served as a antigenic material. Results & discussion. BA in children is characterized by complex etiological structure that combines Gram-positive, Gram-negative and Candida spp. fungi, and their associations. A comparative study of the quantitative composition of the microorganisms isolated from the sputum of the 135 examined children aged 5 to 14 years in the exacerbation period was carried out. It was established that the following microorganisms were isolated from the sputum of the children with ATBA with the lowest frequency: S. pyogenes - 3 (6,8 ± 2,1%), S. aureus - 4 (9,1 ± 2,5%), and Е. coli — 5 (11,4 ± 2,3%); among associations - S. aureus + S. pyogenes - 2 (4,5 ± 1,3%), S. aureus + Pr. mirabilis - 2 (4,5 ±1,3%). The most frequent microorganisms were: С. albicans - 8 (18,2 ± 4,4%), Ps. aeruginosa - 7 (16,0 ± 4,2%), and among associations - S. aureus + Ps. aeruginosa - 4 (9,1 ± 2,5%), and S. aureus + E. coli-3(6,8 ±2,1%). In the children with NABA, the least frequent microorganisms were: С. albicans fungi - 2 (4,4 ± 1,4%), as well as associations: S. aureus + E. coli - 2 (4,4 ± 1,4%), and S. aureus + Pr. mirabilis - 3 (6,7 ± 1,7%), and the most frequent - S. aureus 7 (15,2 ± 3,1%), Ps. aeruginosa - 7 (15,2 ± 3,1%), as well as associations: S. aureus + S. pyogenes - 4 (8,7 ± 2,2 %) и S. aureus + Ps. aeruginosa - 4 (8,72 ± 2,2%). In children with MTBA the lowest frequency of isolation from the sputum was observed for: Рr. mirabilis - 3 (6,5±1,8 %) and Candida spp. fungi - 5 (10,9±4,1 %), among associations - S.aureus + E.coli- 2 (4,3±1,6%); S.aureus + Pr. mirabilis- 3 (6,5±1,8 %), the most frequent microorganisms were: S.aureus - 7 (15,2±3,1 %), Ps.aeraginosa - 7 (15,2±3,1 %), and among associations: S.aureus + S.pyogenes - 4 (8,7±2,2 %), and S.aureus + Ps. aeruginosa -4(8,7±2,2%). The participation of the microflora isolated from the sputum in the etiopathogenesis of the disease can be proven based on the determination in their structure of the mimicry antigens of the trachea, bronchi and lung tissue. It was experimentally proven in course of the study that in NABA the titers of the agglutination of the organ specific serums with Gram-positive microorganisms (Streptococcus and Staphylococcus) were 1:131 — 1:149, which points out their decisive role in the etiopathogenesis in this form of BA, while in the Gram-negative microorganisms, the background values of the titers were observed - 1:17 - 1:85. In MTBA, the agglutination titer of organ specific serums with Gram-positive microorganisms (Streptococcus and Staphylococcus) was in the range (1:128 - 1:213), in Gram-negative microorganisms (E. coli and P. aeruginosa) – (1:64 - 1:160), which points to the participation of the pyogenic and Gram-negative microflora in the etiopathogenesis of this form of BA. In ATBA, the results of agglutination reaction of organ specific serums with Gram-positive microorganisms and Gram-negative microorganisms were in the range of 1:18 - 1:44, the lowest range compared to the NABA and MTBA. It can be concluded that microorganisms, isolated from the children with BA, are able through inclusion into their structure the mimicry antigens of the trachea, bronchi and lung structure, not only to determine the induction of the pathological process, but also to shift it towards autoimmunity. Conclusion. 1.Independent of the BA form in children, the microbial factor has the leading role in its etiopathogenesis, and can lead to the increased severity of the disease course. 2. BA in children is characterized by complex etiological structure that combines Gram-positive, Gram-negative, Candida spp. fungi, and their associations. 3.Microorganisms isolated from the sputum of children with BA, through varying their antigenic potential, are able to include into their structure mimicry antigens of the cellular and tissue structure of the bronchopulmonary system. 4. Microorganisms, through inclusion into their structure the mimicry antigens of the trachea, bronchi and lung structure, not only determine the induction of the pathological process, but also shift it towards autoimmunity.